Dietary Patterns and Nonalcoholic Fatty Liver Disease: A Facility-Based Case–Control Study in Bangladesh (Bioresearch Communications, 2026)
Background: Although diet plays a key role in nonalcoholic fatty liver disease (NAFLD) development, evidence regarding dietary patterns and NAFLD among Bangladeshi adults remains limited. This study examined the association between major dietary patterns and NAFLD in Bangladesh. Methods: A facility-based case-control study was conducted among 400 adults (200 NAFLD cases and 200 controls) recruited from tertiary healthcare facilities in Dhaka, Bangladesh. NAFLD was confirmed using ultrasonography. Dietary intake over the previous month was assessed using a validated semi-quantitative food frequency questionnaire containing 169 food items. Principal component analysis was applied to derive dietary patterns from 24 nutrients and 26 food groups. Multivariable binary logistic regression models were used to estimate adjusted odds ratios (AORs) for the association between dietary pattern quartiles and NAFLD after adjusting for potential confounders. Results: This study found significant differences between cases and controls in terms of physical activity, diabetes prevalence, and body mass index. Furthermore, four food group patterns (energy-dense mixed pattern, fruit and dairy pattern, traditional–processed mixed pattern, and healthy plant-based pattern) and four nutrient patterns (Plant-based micronutrient-rich pattern, animal protein-rich pattern, unsaturated fat-rich pattern, and B-vitamin dominant pattern) were identified, explaining around 67% and 32% of total variance, respectively. The healthy plant-based pattern was inversely associated with NAFLD, with participants in the second quartile having lower odds than those in the lowest quartile (AOR: 0.48; 95% CI: 0.24–0.95). Similarly, unsaturated fat-rich pattern and vitamin E with lower carbohydrate intake were associated with reduced odds of NAFLD in the third quartile (AOR: 0.40; 95% CI: 0.20–0.80). Moreover, the B-vitamin-dominant pattern showed an inverse association in the highest quartile (COR: 0.41; 95% CI: 0.23–0.72), although this association was not significant after adjustment. Conclusion: This study indicates that healthier dietary patterns, rich in whole grains, vegetables, fish, good fats, and antioxidant nutrients, are inversely associated with NAFLD in Bangladeshi adults.  Evidence-based dietary guidelines should be integrated into the national NCD operational manual to support the prevention of NAFLD in Bangladesh.Bioresearch Commu. 12(2): 2148-2161, 2026 (January)